Effects of N-acetylcysteine on liver remote injury after skeletal muscle ischemia reperfusion in rats - Takhtfooladi, Mohammad Ashrafzadeh; Jahanshahi, Gholamreza; Jahanshahi, Amirali; Sotoudeh, Amir; Amlashi, Omidreza Samiee; Allahverdi, Amin (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: This study evaluated the effects of N-acetylcysteine as a scavenger of radical oxygen species on liver injury as a remote organ after skeletal muscle ischemia reperfusion. Materials and Methods: Twenty male Wistar rats were allocated randomly into two experimental groups: ischemia reperfusion (I/R) and ischemia reperfusion + N-acetylcysteine (I/R+NAC). All animals were undergone 2h of ischemia by occlusion femoral artery and 24h of reperfusion. Rats that were treated with N-acetylcysteine given intravenously at a dose of 150 mg/kg, immediately before reperfusion. Serum levels of aspartate aminotransferase (AST), and alanine aminotransferase (ALT) were measured. Livers were harvested for histopathological and biochemical studies. Liver tissue malondialdehyde (MDA), glutathione (GSH) and myeloperoxidase (MPO) activity were assayed. Results: The ALT and AST values were significantly lower in I/R+NAC group. Hepatic MDA level and MPO activity were significantly increased in I/R group. The levels of GSH in liver tissue were significantly depressed by ischemia reperfusion. Liver histopathologic study in I/R group showed enlarged sinusoids, sinusoidal congestion, cytoplasmic vacuolation, cellular degenerative changes and necrosis. Histopathologically, there was a significant difference between two groups. Conclusion: Histopatological and biochemical results have shown that N-acetylcysteine was able to protect liver from skeletal muscle ischemia reperfusion injury.